Neo-hydraulic water management: an international comparison of idle desalination plants. Issue 2 (7th February 2019) - Green, Alice; Bell, Sarah
ABSTRACT: Desalination has been proposed as a solution to water scarcity. However, it is a highly energy intensive and expensive water treatment method, and many new desalination plants remain idle for extended periods. This paper uses qualitative comparative analysis to analyze four cases of idle plants: the Charles E. Meyer Desalination Plant (Santa Barbara, USA), the Kurnell Desalination Plant (Sydney, Australia), the Torrevieja Desalination Plant (Alicante, Spain), and the Thames Gateway Water Treatment Works (London, England). It develops the original concept of neo-hydraulic water management. Neo-hydraulic water management refers to the persistence of capital-intensive, supply-side solutions in response to uncertainty. The increasing role of private capital and the emphasis on treatment technologies, signal new elements of the neo-hydraulic approach as depicted. This paper is significant in its attention to excess desalination capacity, explained by the emergence of neo-hydraulic water management despite global efforts to improve sustainability and integration.